A mixed-methods study of health worker migration from Jamaica. Issue 1 (June 2016) - Tomblin Murphy, Gail; MacKenzie, Adrian; Waysome, Benjamin; Guy-Walker, Joan; Palmer, Rowena; Elliott Rose, Annette; Rigby, Janet; Labonté, Ronald; Bourgeault, Ivy
Abstract Background This study sought to better understand the drivers of migration, its consequences, and the various strategies countries have employed to mitigate its negative impacts. The study was conducted in four countries-Jamaica, India, the Philippines, and South Africa-that have historically been 'sources' of health workers migrating to other countries. The aim of this paper is to present the findings from the Jamaica portion of the study. Methods Data were collected using surveys of Jamaica's generalist and specialist physicians, nurses, midwives, and dental auxiliaries, as well as structured interviews with key informants representing government ministries, professional associations, regional health authorities, healthcare facilities, and educational institutions. Quantitative data were analyzed using descriptive statistics and regression models. Qualitative data were analyzed thematically. Multiple stakeholder engagement workshops were held across Jamaica to share and validate the study findings and discuss implications for the country. Results Migration of health workers from Jamaica continues to be prevalent. Its causes are numerous, long-standing, and systemic, and are largely based around differences in living and working conditions between Jamaica and 'destination' countries. There is minimal formal tracking of health worker migration from Jamaica, making scientific analysis of its consequences difficult. Although there is evidence of numerous national and international efforts to manage and mitigate the negative impacts of migration, there is little evidence of the implementation or effectiveness of such efforts. Potential additional strategies for better managing the migration of Jamaica's health workers include the use of information systems to formally monitor migration, updating the national cadre system for employment of health personnel, ensuring existing personnel management policies, such as bonding, are both clearly understood and equitably enforced, and providing greater formal and informal recognition of health personnel. Conclusion Although historically common, migration of Jamaica's health workers is poorly monitored and understood. Improved management of the migration of Jamaica's health workers requires collaboration from stakeholders across multiple sectors. Indeed, participating stakeholders identified a wide range of potential strategies to better manage migration of Jamaica's health workers, the implementation and testing of which will have potential benefits to Jamaica as well as other 'source' countries.